Algorithmic Identity: Pinterest, Instagram, and the Practices of Curating the Visualization of Self - Raslene, Raslene; Widhiasih, Anggraeni (Bina Nusantara University, 2026)
This research examines how Instagram and Pinterest shape users as creators, curators, and consumers of visual and textual content, influencing behaviors, preferences, and cultural identities. It explores how these platforms integrate images and texts into daily life, creating a